Protective effect of vaginal application of neutralizing and non-neutralizing inhibitory antibodies against vaginal HIV challenge in macaques - Moog, C (2014)
Definition of antibody (Ab) functions capable of preventing mucosal HIV transmission may be critical to both effective vaccine development and the prophylactic use of monoclonal Abs. Although direct antibody-mediated neutralization is highly effective against cell-free virus, increasing evidence suggests an important role for immunoglobulin G (IgG) Fcc receptor (FccR)–mediated inhibition of HIV replication. Thus, a panel of well-known neutralizing (NAbs) and nonneutralizing Abs (NoNAbs) were screened for their ability to block HIV acquisition and replication in vitro in either an independent or FccR-dependent manner. Abs displaying the highest Fc-mediated inhibitory activity in various in vitro assays were selected, formulated for topical vaginal application in a microbicide gel, and tested for their antiviral activity against SHIVSF162P3 vaginal challenge in non-human primates (NHPs). A combination of three NAbs, 2G12, 2F5, and 4E10, fully prevented simian/human immunodeficiency virus (SHIV) vaginal transmission in 10 out of 15 treated NHPs, whereas a combination of two NoNAbs, 246-D and 4B3, although having no impact on SHIV acquisition, reduced plasma viral load. These results indicate that anti-HIV Abs with distinct neutralization and inhibitory functions differentially affect in vivo HIV acquisition and replication, by interfering with early viral replication and dissemination. Therefore, combining diverse Ab properties may potentiate the protective effects of anti-HIV-Ab-based strategies.